Morphological Variation of Rafflesia zollingeriana Koord. and its Recent Distribution in East Java, Indonesia - Dewi Lestari; Agus Susatya (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2022)
Locals in Lumajang have reported the growth of Rafflesia in Tempursari and Pasirian. Because species identification is fundamental for ecological monitoring, this study aims to identify species and record its geographical distribution. The Rafflesia at two locations were identified as R. zollingeriana after observing the specimens at the site and comparing them to herbaria from THBB and PHPB. This signifies that the distribution of R. zollingeriana in East Java has been updated. R. zollingeriana was formerly thought to only exist in conservation areas like Meru Betiri National Park and Watangan Nature Reserve, but this research demonstrates that it also exists outside of these protected/conservation areas. Only hills and steep cliffs are home to R. zollingeriana in Lumajang. This extremely limited and tough environment is assumed as a result of the conversion of forests into agricultural plantation, which only remained these sites for R. zollingeriana to grow. In order to prevent R. zollingeriana extinction in these areas, conservation strategies are required. This study offers conservation strategy recommendations, both in situ and ex situ. These recommendations expected could be used to establish a long-term conservation strategy for East Java's Rafflesia.